The status of occupational safety among health service providers in hospitals in Tanzania - Manyele, SV; Ngonyani, HAM; Eliakimu, E (Tanzania Journal of Health Research, 2008)
Occupational hazards exist wherever health care is practised. However, there is dearth of information on the status of occupational safety among hospital workers in Tanzania. This study was therefore carried to assess the current status of occupational health and safety (OHS) in Tanzanian hospitals and identify key areas for intervention. Data was collected using a self-administered questionnaire randomly distributed to the health service providers (HSPs) working in 14 district, regional and referral hospitals in Tanzania. A total of 430 HSPs (mean age = 42±8.8 years) were involved in the study. Female workers accounted for the majority (71%) of the respondents. None of the 430 respondents had received training on OHS as a profession. Most of the supervisors were holdersof certificates (54.4%). Only 42.9% (6/14) of the hospitals, had at least a supervisor with post-graduate degree. Needlestick injuries accounted for the largest part of the most common accidents (52.9%); followed by splash of blood from patients (21.7%); burn injury from chemicals (10.6%); and slippery floors (5.9%). There was lack of qualified personnel for OHS in all hospitals. Most of the hazardous activities were carried out by nurses and attendants. Chemicals used in hospitals were mainly antiseptics and disinfectants, which causes skin burns during handling and use. Seminars and workshops were the major source (N = 429; 33%) of information on OHS. The seven major hazardous activities were injection, cleaning, patient care, bedding, dressing of wounds, medication and surgical operation. The largest proportion of HSPs involved in hazardous activities was found at referral hospitals. The mostly available antiseptics were 70-90% alcohol, 3% aqueous iodine, chlorhexidine gluconate and cetrimide. In conclusion, the OHS was observed to be inadequate in most workplaces in Tanzanian hospitals. Special efforts including training, exposure to information and creation of awareness, are recommended for improvingoccupational health and safety in hospitals in Tanzania. Keywords: occupational health, safety, hospital, Tanzania Tanzania Journal of Health Research Vol. 10 (3) 2008: pp. 159-165